You are on page 1of 11

GAUSS JORDAN

Solucin:

F1/-2
-2

18

-1/2

-3

-9

-16

-16

-10

-3

-10

-3

F2/5/2

F2= -5*f1+f2
F3= -3*f1+f3

-1/2

-3

-9

5/2

23

29

7/2

-1

24

F3/-166/5

F3= -7/2*f2+f3

-1/2

-3

-9

-1/2

-3

-9

-1/2

-3

-9

46/5

58/5

46/5

58/5

46/5

58/5

7/2

-1

24

-166/5

-83/5

1/2

F1=-3*f3+f1

F2=-46/5*f3+f2

F1=1/2*f2+f1

-1/2

-3

-9

-1/2

15/2

-4

1/2

1/2

X1=-4
X2= 7
X3=1/2

1/2

F3=-1*f1+f3

F1/-1
-1

-1

-1

-1

-3

-1

-3

-1

-3

F3= f2+f3

F2= -3*f3+f2

F3/4

-1

-1

-1

5/2

-2

-1/2

-1/2

-1/2

F1= f3+f1
1

X1=-1/2
X2= 5/2

5/2

-1/2

X3=-1/2

F1/3

F3= f1+f3

F2= -2*f1+f2

-6

-2

-2

-5

-5

-9

-1

16

-14

-3

-1

16

-14

-3

18

-16

F3= -18*f2+f3

F2/-9

F1= -2*f2+f1

-2

-2

-2/9

-8/9

-8/9

-8/9

18

-16

F2= -2*f1+f2

F3= -5*f1+f3

-6

-5

28

-26

-8

F2/3

F2/-9

-2

-5

28

-26

-8

F3=-18*f2+f3

-2

-2

-2

-9

-8/9

-8/9

18

-16

-23

18

-16

-23

-23

F3/-23

F1= -3*F3+F1

F1= -2*F2+F1

-2

-2

-2/9

-8/9

-8/9

-8/9

F1/-2

F3= -1*f1+f3

F2=f1+f2

-2

-6

-3

3/2

-9/2

-1

-1

-1

-1

-1

-1

F2/4

F3= 4*f2+f3

3/2

-9/2

3/2

-9/2

3/2

-9/2

1/2

-7/2

1/8

-7/8

1/8

-7/8

-4

1/2

13/2

-4

1/2

13/2

F1= -3*f2+f1

F1= -3/2*f3+f1

F2=-1/8*f3+f2
1

3/2

-9/2

-9

-21/4

-5/4

-5/4

-5/4

X1=-21/4
X2= -5/4
X3= 3

F2= -4*f1+f2
1

-1

-1

-1

-5

-24

-3

-1

-14

F3/-1

F2/-5

F3= -2*f1+f3

F2= 9/5*f3+f2

-1

-1

-1

-9/5

24/5

-9/5

24/5

30

-1

-14

14

14

F1= -1*f2+ f1

F1= f3+ f1
1

21

-9

30

30

14

14

X1= -9
X2= 30
X3= 14

F2= -4*f1+f2
1

-1

-1

-1

-5

-24

18

-5

-24

F3= 5*f2+f3

F2/-5

F3= -6*f1+f3

F1= -1*f2+f1

-1

-1

4/5

11/5

-9/5

24/5

-9/5

24/5

-9/5

24/5

-5

-24

F3= -6*f1+f3

F2= -4*f1+f2
1

-1

-1

-1

-5

-24

20

-5

-22

F3= 5*f2+f3

F2/-5

F3/2

-1

-1

-1

-9/5

24/5

-9/5

24/5

-9/5

24/5

-5

-22

F2= -24/5*f3+f2

F1= -1*f2+f1

F1= -7*f3+f1

-1

-1

4/5

-9/5

-9/5

-9/5

F3= -2*f1+f3

F2= -4*f1+f2
1

-2

-2

-1

-13

-1

-3

F3/4/3

F3= -3*f2+f3

F2/9
1

-2

-2

-2

-13/9

-13/9

-13/9

-3

4/3

F1= -3*f3+f1

F2= 13/9*f3+f2

F1= 2*f2+f1

-2

-2

X1= 0
X2= 0
X3= 0

F1/-2

F2= 3*f1+f2

F3= -5*f1+f3

-2

-1

1/2

-3/2

-3

-1

-3

-1

0
F3/10

F3= -1/2*f2+f3

F2/11/2

1/2

-3/2

1/2

-3/2

1/2

-3/2

1/2

-3/2

11/2

-11/2

-1

-1

-1

1/2

19/2

1/2

19/2

10

F1=3/2*f3+f1

F2= f3+f2

F2= f3+f2

F1=-1/2*f2+f1

1/2

-3/2

1/2

-3/2

1/2

F2= -4*f1+f2

F2/-5

F3= -6*f1+f3

-1

-1

-1

-5

-5

F1= -1*f2+f1

F3= 5*f2+f3

-1

-1

4/5

-9/5

-9/5

-9/5

-5

MATRIZ INVERSA

FALSO = F

=V
=F
=V
=V
=F
=F

SOLUCIN
F2= -3*F1+F2

F1/2
2

1/2

1/2

1/2

1/2

1/2

-3/2

F1= -1/2*F2+F1

F2/1/2
1

1/2

1/2

-1

-3

-3

F2= -3*F1+F2
1

-2

-3

F1= -2*F2+F1

F2/-2
1

3/2 -1/2

-2

3/2 -1/2

F3=-5*F1+F3
1

-4

-5

F2/2

F2=-3/2*F3+F2

F3/-4

3/2

1/2

3/2

1/2

-15/8

1/2

3/8

-4

-5

5/4

-1/4

5/4

-1/4

F1=-1*F2+F1

F1=-1*F3+F1
1

-1/4

1/4

17/8

-1/2

-1/8

-15/8

1/2

3/8

-15/8

1/2

3/8

5/4

-1/4

5/4

-1/4

F1/3
3

2/3

1/3

1/3

-1

-1

F3/-1

F2/2

F2= -1*f3+f2

2/3

1/3

1/3

2/3

1/3

1/3

2/3

1/3

1/3

1/2

1/2

1/2

-1

-1

-1

F1=-1/3*f3+f1

F1=-2/3*f2+f1

2/3

1/3

1/3

1/3

-1/3

1/3

1/2

1/2

-1

-1

-1

-1

Intercambiar

-1

-1

F1 * f3

F3= f2+f3

F2= f3+f2

F3/-1

-1

-1

-1

-1

-1

-1

-1

-1

F1=-1*f3+f1
1

-1

-1

-1

0
F2/2
2

1/2

-1

-1

F3=-3*f1+f3

F3/-4

F3= f2+f3

1/2

1/2

1/2

-1

-5

-3/2

-4

-3/2

3/8

F2=-1*f3+f2

F1=-2*f3+f1

1/2

-1/4

1/2

1/2

-3/8

5/4

1/4

-3/8

5/4

1/4

3/8

-1/4 -1/4

3/8

-1/4 -1/4

-1/4 -1/4